SEJARAH PERKEMBANGAN PEMIKIRAN USHULFIQH (Analisis Legislasi Hukum Islam Dalam Lintas Sejarah) - Irkham Afifianto (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2013)
Idea of Islamic study reechoing lickety split in Islam world prove, that Islam as a experience of diaspora which do not be barricaded. Reconditional movement of idea with various its pattern a undoubtedly history. Therefore movement idea of Islamic study will always follow history motion that happened that moment. So, that Islam is blessing religion of lil’alamin accomplishment to all life manual fight poorness, and realize prosperity in all human life aspect and also lift unemployment. In the field of Islam economics property of orders representing fringes in transaction with model which have been determined and enabled, like merchant, message, pawn, transfer of, association, federation of trade association and farmer. In accomplishment to problem of sosial-keagamaan above, hence from that we need solution in around method or peripheral in searching solution problems of life that happened around us. In this case according to economizing writer that is us shall have knowledge science of ushul sources and fiqh intake of law or which is frequent to be known as al-Syari Mashadir’ or al-Ahkam ushul or of Adillat al-Ahkam, as peripheral which we require in accomplishment of our life intention